Cereal-legume intercropping for managing erosion in arid soil - Machiwal, Deepesh; Kumar, Sushil; Kumar, Sanjay (Indian Farming, 2022)
Kachchh district in Gujarat is mostly known for soil salinity with presence of two large salty marshlands, i.e. the Great and the Little Rann. However, the fact is that the lands in Kachchh are mainly degraded due to soil erosion under the changing climate, and salinity counts afterwards. Erosion of soil further results in loss of nutrients from the fertile top soil, and thus, declining crop productivity. Cultivation of sole cereal crops is a common practice in the region, which results in huge amount of soil and nutrient losses from limited soil depths. Legume crops like green gram and cluster bean may be suitably intercropped with cereal crops of sorghum and pearl millet in 2:1 cereal-legume row ratio to check soil loss and conserve soil nutrients.